If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3k = 2(k + 7) Reorder the terms: 3k = 2(7 + k) 3k = (7 * 2 + k * 2) 3k = (14 + 2k) Solving 3k = 14 + 2k Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-2k' to each side of the equation. 3k + -2k = 14 + 2k + -2k Combine like terms: 3k + -2k = 1k 1k = 14 + 2k + -2k Combine like terms: 2k + -2k = 0 1k = 14 + 0 1k = 14 Divide each side by '1'. k = 14 Simplifying k = 14
| 2m^2+5m=2 | | x^2+60=2x+15 | | 17=x | | -5x+7y=10 | | 4(2-3x)+10(x-2)=7 | | -6g+12=12g+12 | | -7(6x+10)=-154 | | 90=2(x^2+60) | | x^6-5x^5-6x^4=0 | | 2x+x=4x | | 3-(12+2x)-6x=15-2x | | (3x+5)-7=0 | | 900000+111111= | | 4y=12-3x | | 2(-9+5x)=52 | | 2(-9+5x)=53 | | 2x-12-2x=4x-12 | | 1/32*12=s | | 3x^4-10x^3-24x^2-6x+5=0 | | 6u^2=-9u | | x-48.12=28.82 | | 6x^2=-9u | | 1.203125=1.375v | | 15g-4=36 | | [x+2]-7=5 | | 1=-3+2x | | -7(4x+7)=-77 | | [x]-10.5=4.3 | | 2(-4h-13)=37*13h | | 3(6z-1)-4(z+5)=7(z+1) | | 4x+12-x-1=1 | | n-31=9 |